2015
DOI: 10.1073/pnas.1510662112
|View full text |Cite
|
Sign up to set email alerts
|

Musical expertise is related to altered functional connectivity during audiovisual integration

Abstract: The present study investigated the cortical large-scale functional network underpinning audiovisual integration via magnetoencephalographic recordings. The reorganization of this network related to long-term musical training was investigated by comparing musicians to nonmusicians. Connectivity was calculated on the basis of the estimated mutual information of the sources' activity, and the corresponding networks were statistically compared. Nonmusicians' results indicated that the cortical network associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 50 publications
7
40
1
Order By: Relevance
“…Furthermore, superior temporal lobe structures in musicians showed different connectivity patterns from MMT controls: Classical musicians had significant connectivity from RECN to bilateral temporal pole which was not seen in the other two groups, whereas Improvisational musicians had higher connectivity than MMT controls between vDMN seed and left temporal pole, precuneus network seed and left temporal pole, and primary visual network seed and left middle and inferior temporal gyri. The latter is consistent with magnetoencephalography work showing that musicians have more densely connected cortical network that enables audiovisual integration (Paraskevopoulos et. al., 2015).…”
Section: Differences In Resting State Connectivity Related To Generalsupporting
confidence: 89%
“…Furthermore, superior temporal lobe structures in musicians showed different connectivity patterns from MMT controls: Classical musicians had significant connectivity from RECN to bilateral temporal pole which was not seen in the other two groups, whereas Improvisational musicians had higher connectivity than MMT controls between vDMN seed and left temporal pole, precuneus network seed and left temporal pole, and primary visual network seed and left middle and inferior temporal gyri. The latter is consistent with magnetoencephalography work showing that musicians have more densely connected cortical network that enables audiovisual integration (Paraskevopoulos et. al., 2015).…”
Section: Differences In Resting State Connectivity Related To Generalsupporting
confidence: 89%
“…Unfortunately, we are aware of no study to date which has examined potential music-induced differences in brain connectivity between primary auditory and visual brain regions that would presumably mediate the doubleflash illusion (cf. Paraskevopoulos et al 2015). However, in musically lay individuals, prior studies have indicated that the likelihood of perceiving the double-flash illusion is highly correlated with white matter connectivity between occipito-parietal regions, the putative ventral/dorsal streams comprising the "what/where" pathways (Kaposvari et al 2015).…”
Section: Experience-dependent Changes In Multisensory Perceptionmentioning
confidence: 99%
“…In this study, we compared novel word learning in musicians and nonmusicians by using three concatenated tasks that are dependent upon a variety of perceptual and cognitive functions typically involved in both music and language processing (Dittinger et al, 2016). Based on previous evidence pointing to an optimization of perceptual discrimination (Chobert et al, 2014;Marie et al, 2011), short-term and working memory (George & Coch, 2011;Schulze & Koelsch, 2012), executive functions (Zuk et al, 2014), and audiovisual integration (Bidelman, 2016;Paraskevopoulos, Kraneburg, Herholz, Bamidis, & Pantev, 2015) in musicians, we predicted that the musicians' advantage in word learning would translate into increased EEG-based functional connectivity along the ventral-and dorsal processing streams. Results consistently revealed increased beta coherence in the ventral compared to the dorsal stream during both the "matching-" and "semantic tasks."…”
Section: Discussionmentioning
confidence: 99%